Aesthetic modification of labial frenectomy technique in Graber-positive frenum with low insertion. Case report - Gonzales-Mendozal, Julio (2024)
Objective: To describe the aesthetic modification of the surgical technique for upper labial frenulum (frenectomy) to preserve the interdental papilla of vestibular frenulum with low insertion. Case report: A female 9-year-1-month-old patient attended the Dental Clinic of Universidad Científica del Sur, Lima-Peru. Clinical examination revealed a low insertion of upper labial frenulum, and the presence of a central diastema diagnosed as positive in the Graber test. After local dental anesthesia, a modified “Y” shaped incision was made to preserve the interdental papilla. Then, the papilla was divided using a split-thickness papillary flap technique with the complete removal of the transgingival alveolar fiber. Total elimination of the papilla was avoided. The rhomboidal incision and the papillary flap were sutured, respectively. This improved the final aesthetic outcome of the clinical conditions. Conclusion: The aesthetic modification of the surgical technique for upper labial frenulum allows to address the cause of the central diastema, improving surgical technique to provide better aesthetics. This technique also prevents the recurrence due to incomplete surgical technique in this type of frenulum.